2012
DOI: 10.1007/s12013-012-9423-5
|View full text |Cite
|
Sign up to set email alerts
|

Perifosine Induces Cell Apoptosis in Human Osteosarcoma Cells: New Implication for Osteosarcoma Therapy?

Abstract: Despite the advances of adjuvant chemotherapy and significant improvement of survival, the prognosis for patients with osteosarcoma is generally poor. The search for more effective anti-osteosarcoma agents is necessary and urgent. Here we report that perifosine induces cell apoptosis and growth inhibition in cultured human osteosarcoma cells. Perifosine blocks Akt/mTOR complex 1 (mTORC1) signaling, while promoting caspase-3, c-Jun N-terminal kinases (JNK), and p53 activation. Further, perifosine inhibits survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…For example, perifosine could activate pro-apoptotic JNK in various cancer cell lines [24,34,35]. Inhibition of JNK, both pharmacologically or genetically, then alleviated perifosine-induced cancer cell apoptosis [34,35]. Several studies demonstrated that perifosine could inhibit ERK activation, but that effect was cell line dependent [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…For example, perifosine could activate pro-apoptotic JNK in various cancer cell lines [24,34,35]. Inhibition of JNK, both pharmacologically or genetically, then alleviated perifosine-induced cancer cell apoptosis [34,35]. Several studies demonstrated that perifosine could inhibit ERK activation, but that effect was cell line dependent [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…U2OS and MG-63 osteoblastoma cells as well as HEK-293T were gifts from Dr. Zhang-Ping Gu at Nanjing Medical University [48,49], cells were maintained in DMEM (Sigma, St. Louis, MO), supplemented with a 10% FBS (Sigma) plus penicillin/streptomycin (1:100; Sigma), in a CO 2  incubator at 37 °C. …”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, despite not achieving the primary objectives related to significant increases in progression-free survival rates, some optimism still remained for this agent in advanced soft tissue sarcoma patients (Bailey, et al, 2006), as well as to warrant further evaluation of perifosine in combination with rituximab or other active agents in patients with relapsed/refractory Waldenstrom's macroglobulinemia (Ghobrial, et al, 2010), and with currently available therapies in renal cancer (Cho, et al, 2012). Furthermore, a number of studies have reported the potentiation of antitumor activity following combination of perifosine with distinct anticancer drugs in cancer cells derived from several types of leukemia (Nyakern, et al, 2006;Papa, et al, 2008;Tazzari, et al, 2008), multiple myeloma Hideshima, et al, 2006), osteosarcoma (Yao, et al, 2013), medulloblastoma (Kumar, et al, 2009), lung cancer (Elrod, et al, 2007), colon cancer (M. B. Chen, et al, 2012, and glioma (Momota, et al, 2005), as well as following combination of miltefosine with different anticancer compounds or treatments in distinct cancer cell types (Haberkorn, et al, 1992;Papagiannaros, et al, 2006;Spruss, et al, 1993;Thakur, et al, 2013). Thus, phase II clinical trials were conducted with…”
Section: Alkylphosphocholinesmentioning
confidence: 99%